McXtrace: a Monte Carlo software package for simulating X‐ray optics, beamlines and experiments. (15th May 2013) - Bergbäck Knudsen, Erik; Prodi, Andrea; Baltser, Jana; Thomsen, Maria; Kjær Willendrup, Peter; Sanchez del Rio, Manuel; Ferrero, Claudio; Farhi, Emmanuel; Haldrup, Kristoffer; Vickery, Anette; Feidenhans'l, Robert; Mortensen, Kell; et al.
Abstract : This article presents the Monte Carlo simulation package McXtrace, intended for optimizing X‐ray beam instrumentation and performing virtual X‐ray experiments for data analysis. The system shares a structure and code base with the popular neutron simulation code McStas and is a good complement to the standard X‐ray simulation software SHADOW . McXtrace is open source, licensed under the General Public License, and does not require the user to have access to any proprietary software for its operation. The structure of the software is described in detail, and various examples are given to showcase the versatility of the McXtrace procedure and outline a possible route to using Monte Carlo simulations in data analysis to gain new scientific insights. The studies performed span a range of X‐ray experimental techniques: absorption tomography, powder diffraction, single‐crystal diffraction and pump‐and‐probe experiments. Simulation studies are compared with experimental data and theoretical calculations. Furthermore, the simulation capabilities for computing coherent X‐ray beam properties and a comparison with basic diffraction theory are presented.